Does California's CO2 price affect wholesale electricity prices in the Western U.S.A.?. (November 2017) - Woo, C.K.; Olson, A.; Chen, Y.; Moore, J.; Schlag, N.; Ong, A.; Ho, T.
Abstract: Using a sample of daily market data, we quantify the effect of California's CO2 cap-and-trade program on the wholesale electricity prices of four interconnected market hubs in the Western U.S.A.: North of Path 15 (NP15) and South of Path 15 (SP15) in California, Mid-Columbia (Mid-C) in the Pacific Northwest, and Palo Verde (PV) in the Desert Southwest. A $1/metric ton increase in California's CO2 price is estimated to have increased the electricity prices by $0.41/MWh ( p -value < 0.0001) for NP15, $0.59/MWh ( p -value < 0.0001) for SP15, $0.41/MWh ( p -value = 0.0056) for Mid-C, and $0.15/MWh ( p -value = 0.0925) for PV. These estimates reflect: (a) the NP15 and SP15 sellers' pricing behavior of fully including the CO2 price in their intra-state transactions; (b) the Mid-C price's 100% pass-through of the CO2 price in the Pacific Northwest's hydro export to California; and (c) the statutory obligation of paying the CO2 emissions cost by California's buyers of the electricity imported from the Desert Southwest. The policy implication is that internalization of CO2 's externality in the Western U.S.A. requires a cap-and-trade program with a regional scope that encompasses all four hubs, thereby remedying the California program's limited geographic coverage which introduces distortions in neighboring markets. Highlights: Estimate California's CO2 price's effect on electricity prices in the Western U.S. Document statistically significant effects of California's cap-and-trade program. Report the CO2 price's full pass-through in California and the Pacific Northwest. Report the CO2 price's insignificant pass-through in the Desert Southwest. Discuss the policy implications of the California program in the Western U.S.